THE INFLUENCE OF ENHYPEN AS A BRAND AMBASSADOR AND ELECTRONIC WORD-OF-MOUTH (EWOM) ON PURCHASE DECISION TOWARDS NABATI PRODUCT (A STUDY AMONG @NABATI_ID INSTAGRAM FOLLOWERS) - Kalumata, Lisy Militia Christy Gracia; Mangantar, Maryam; Tumewu, Ferdinand (Universitas Sam Ratulangi, 2024)
This research aimed to analyze The Influence of ENHYPEN as a Brand Ambassador and Electronic Word-of-Mouth (eWOM) on Purchase Decision towards Nabati Product, simultaneously or partially. The research variables consist of X1 which is Brand Ambassador, X2 which is Electronic Word-of-Mouth (eWOM0, and Y which is Purchase Decision. Data resource is from primary data, obtained from the questionnaire distribution with Likert scale. The sample of this research was Engenes (ENHYPEN fans) who are following @nabati_id on Instagram and those who already purchased Nabati, with the total 100 respondents. The test instruments are Validity and Reliability Test using SPSS 29. Technique analysis using Multiple Linear Regression Analysis, Classical Assumption Test, and Hypothesis Test. The result showed that ENHYPEN as a Brand Ambassador has a significant influence towards Purchase Decision, as well as Electronic Word-of-Mouth also has a significant influence on Purchase Decision. Both Brand Ambassador and Electronic Word-of-Mouth have a positive influence towards Purchase Decision. Keywords: Brand Ambassador, Electronic Word-of-Mouth, eWOM, Purchase Decision